Pengaruh Professional Skepticism dan Time Budget Pressure terhadap Audit Quality dimoderasi Variabel Remote Audit pada Auditor BPK Perwakilan Provinsi Bengkulu - Nainggolan, Citra Anggreiny (Universitas Bengkulu, 2025)
This study aims to analyze the impact of professional skepticism and time budget pressure on audit quality, with remote audit as a moderating variable, focusing on auditors at the BPK Representative Office in Bengkulu. The research employs a quantitative causal method, collecting data through a closed questionnaire distributed online to 95 auditors. The data was analyzed using SPSS. The findings indicate that professional skepticism has a positive and significant effect on audit quality, as auditors with higher skepticism tend to be more thorough in gathering audit evidence, thereby improving audit quality. Time budget pressure, however, does not significantly affect audit quality, suggesting that auditors are able to manage time constraints without compromising their work. Remote audits weaken the relationship between professional skepticism and audit quality due to limited direct access to physical audit evidence as well as barriers in communication that can reduce the auditor's ability to fully implement their skeptical attitude. Overall, the combination of professional skepticism, effective time management, and the use of remote audit technology plays a crucial role in maintaining audit quality. Recommendations include enhancing auditor competencies, better time management, investing in technology to support remote audits, and continuous evaluation of the effectiveness of remote audits in improving audit processes.